Risk Factors Associated With Contact Dermatitis in Scavengers - Dariswan, Dinda Tiara Nurzahrah; Azizah, R. (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2026)
Contact dermatitis is a common occupational skin disorder among scavengers due to frequent exposure to irritants and allergens in hazardous working environments. This review aims to analyze the association between personal hygiene, duration of work, and the use of personal protective equipment (PPE) with the incidence of contact dermatitis among scavengers. A systematic literature review was conducted using ten relevant journal articles published within the last five years and retrieved from Google Scholar. The findings consistently indicate a significant association between poor personal hygiene and an increased risk of contact dermatitis (p < 0.05), with scavengers exhibiting inadequate hygiene practices experiencing skin complaints 8.5 times more frequently than those maintaining good hygiene. Prolonged duration of contact and longer employment periods were also found to significantly contribute to the incidence of dermatitis, as extended exposure to irritants exacerbates skin damage. In addition, inadequate use of PPE showed a strong correlation with higher rates of contact dermatitis, highlighting the protective role of physical barriers in preventing direct exposure to harmful substances. Age and sex were also identified as contributing factors, reflecting physiological differences in skin sensitivity and immune response. This review underscores the importance of targeted interventions, including the promotion of proper personal hygiene, consistent use of PPE, and regulation of working duration, to effectively reduce the incidence of contact dermatitis among scavengers. The findings provide comprehensive insights and preventive recommendations to enhance occupational health management for this vulnerable worker population.